A Meta-Analysis to Determine Protein and Energy Requirements for Maintenance and Growth of Cattle in Indonesia - Samadi, Samadi; Wajizah, Sitti; Yuliansyah, Andika Boy; Ilham; Jayanegara, Anuraga (ANIMAL PRODUCTION, 2024)
The meta-analysis in this study was conducted to determine the protein and energy requirements of various cattle breeds in Indonesia. A database was compiled from various research articles that involved cattle as the experimental animals, focusing on studies that reported energy and protein intake, initial body weight, and average daily gain (ADG). In total, 57 articles covering different cattle breeds in Indonesia, with 191 data points, were integrated into the database. The database specified different breeds (Aceh, Bali, Madura, Peranakan Ongole (PO), Sumba Ongole (SO), and Local) and sexes. Regressing ADG used to determine maintenance and gain requirements of dry matter, energy, and protein with dry matter intake (DMI), total digestible nutrient intake (TDNI), and crude protein intake (CPI), respectively. An intercept (where ADG= 0 kg/kg MBW/d) and a slope (required nutrient intake per unit ADG) were taken as maintenance and gain requirements, respectively. Results revealed that protein and energy requirement for maintenance (CPm and TDNm) of all cattle breeds varied in values, ranging from 0.0014 to 0.0102 kg/kg MBW/d (Madura and PO breeds) and 0.0232 to 0.0687 kg/kg MBW/d (Aceh and PO breeds), respectively. Each cattle breed in Indonesia has its particular CP and TDN requirements. Both energy and protein requirements for maintenance (CPm and TDNm) and gain (CPg and TDNg) varied in value for each breed.